New Cercospora spp. from north-eastern Uttar Pradesh - and NISHA KUMARI, R.K. SRIVASTAVA, S. NARAYAN (Indian Phytopathology, 2002)
Four new species of Cercospora viz; C. aeruae, C. nyctanthidis, C. acimigena, C. triumfettae-rhomboideae occurring on Aerua scandens, Nyctanthis arbor-tristis. Ocimum sanctum and Triumfetta rhomboidea, respectively are descrived and illustrated.